Social mobility and the social representation of sparkling wine in Brazil and France - Marcos V. Araújo; Grégory Lo Monaco; Kelly Lissandra Bruch (Wine Economics and Policy, 2021)
Wine is a social object, established in the Old World and later migrated to the New World. Champagne is an internationally important and famous French sparkling wine, significantly present worldwide. Brazil, a New-World wine producer, has a recent but expanding history of sparkling wine production and consumption. As to its social aspect, this product has different representations and roles in both these countries. Therefore, this study aims to understand how culture and social status influence the organization of social representations associated with sparkling wines in Brazil and France. Thus, we used the Social Representation approach, a theory of knowledge and communication. For content collection, we carried out a verbal association task. Two hundred and thirteen Brazilians and one hundred ninety-eight French participants provided the first four words which came to mind after hearing four inducted words. The verbal associations were categorized using semantic contextualization. Then, we performed a Correspondence Factor Analysis. The results supported our hypothesis that culture, social status, and social origins all influence social representations associated with sparkling wine, revealing this kind of wine to be a product of social distinction and affluence.
Keywords: 330; Social Origins; social representation; wine culture; social norms; wine consumption